Pendidikan Tinggi dalam Islam - Syafi’i, Asrop (Taallum: Jurnal Pendidikan Islam, 2013)
The stagnant of Islam is started with the abolition of Khalifah system in governance and the division of kingdom as province by which it raised the spirit of raising independent nations. The nations then separate information and knowledge so that the syekh do not get full authority in developing scientific community or halaqoh. The reformation of Islam does not only function as a bridge from the tradition of Greece and new Islam but it develop knowledge by using different tradition among Muslim scholars.